2015
DOI: 10.1111/jonm.12288
|View full text |Cite
|
Sign up to set email alerts
|

The influence of empowerment, authentic leadership, and professional practice environments on nurses’ perceived interprofessional collaboration

Abstract: Nurse leaders who ensure access to resources such as knowledge of IPC, embody authenticity and build trust among nurses, and support the presence of a professional nursing practice environment can contribute to enhanced IPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 40 publications
10
105
0
9
Order By: Relevance
“…In one study conducted with nurses in hospitals, researchers found that nurses' autonomy did not undermine teamwork between nurses and physicians, but rather, improved it. 27 Leadership can play a vital role in promoting teamwork 28,29 by engaging members into collaborative efforts and changing the organizational structures to better meet patients' and providers' needs. 22,30,31 Despite the attention in recent years on primary care teams, we lack empirical evidence about how to promote teamwork.…”
Section: Introductionmentioning
confidence: 99%
“…In one study conducted with nurses in hospitals, researchers found that nurses' autonomy did not undermine teamwork between nurses and physicians, but rather, improved it. 27 Leadership can play a vital role in promoting teamwork 28,29 by engaging members into collaborative efforts and changing the organizational structures to better meet patients' and providers' needs. 22,30,31 Despite the attention in recent years on primary care teams, we lack empirical evidence about how to promote teamwork.…”
Section: Introductionmentioning
confidence: 99%
“…[69][70][71] The presence of a nurse manager who is visible and communicates effectively, strengthens the organisational structure and protects the work environment reducing the risks associated with burnout. [27,72] A potentially positive influence of the hot-floor model was in relation to nurses being less likely to be redeployed to external wards on a short-term shift-by-shift basis than those in the conventional ICU. Intensive care nurses possess a broad range of skills applicable to complex patients in a majority of clinical specialties, and as such are highly mobile across the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…It is important that although it is a collaborative environment, individual team members still feel supported and recognized in their professional role (Regan et al, 2016). Working collaboratively requires time to engage with others, so adequate staffing is also important to relieve time constraints for professionals and administrative support can help with documentation and organizational tasks (van Dongen et al, 2016;Orchard et al, 2005;Regan et al, 2016).…”
Section: Fundamentals Of Interprofessional Educational and Collaboratmentioning
confidence: 99%
“…Professionals should be provided time, information, support, and space to engage in collaborative practice and encourage feedback from peers (Orchard, 2010;Regan et al, 2016). It is important that although it is a collaborative environment, individual team members still feel supported and recognized in their professional role (Regan et al, 2016).…”
Section: Fundamentals Of Interprofessional Educational and Collaboratmentioning
confidence: 99%
See 1 more Smart Citation